Child Labor under Cash and In-Kind Transfers. (19th May 2022) - Tagliati, Federico
Abstract: This paper studies the effects of cash versus in-kind transfers on the time allocation of children exploiting the randomized rollout of a program which transferred either cash or a basket of food to poor households in Mexico. Children in cash-recipient households experience a significantly larger decrease in paid employment and hours of work, and an increase in schooling, as compared to children in in-kind-recipient households. Both transfers are given to a female member of the household to enhance women's participation in household decision-making. The difference between the cash and in-kind impacts on child time allocation is entirely driven by households presenting characteristics associated with lower female decision-making power. Thus, differences in child employment responses across transfer modalities are likely related to women-targeted transfers having larger effects on female empowerment when provided in cash.